Asymmetric Synthesis of Fluorinated Monoterpenic Alkaloid Derivatives from Chiral Fluoroalkyl Aldimines via the Pauson‐Khand Reaction. Issue 6 (3rd February 2020) - Llobat, Alberto; Sedgwick, Daniel M.; Cabré, Albert; Román, Raquel; Mateu, Natalia; Escorihuela, Jorge; Medio‐Simón, Mercedes; Soloshonok, Vadim; Han, Jianlin; Riera, Antoni; Fustero, Santos
Abstract: Enantioenriched fluorinated monoterpenic alkaloid analogues were synthesised, employing a strategy based on the previously undescribed diastereoselective propargylation of fluorinated tert ‐butanesulfinyl imines, and subsequent Pauson‐Khand reaction of resulting enyne derivatives, carried out both stoichiometrically and catalytically. The Pauson‐Khand reaction tolerated both substituted alkenes and alkynes, and took place in good yields and diastereoselectivities, even when applied to a gram‐scale synthesis. Abstract :